PENYULUHAN DAN PEMBINAAN KADER DALAM PENDATAAN STUNTING DI PUSKESMAS TEUPIN RAYA TAHUN 2021 - Zaitun Zaitun; Salamah Salamah; Ajirna Dewi (COVIT (Community Service of Health), 2021)
Short children (stunting) is one of the nutritional problems faced in the world, especially in poor and developing countries. Stunting is a problem because it is associated with an increased risk of morbidity. Stunting is caused by a long-term lack of nutrition during the first 1000 days of life (HPK), which is a critical period. 1000 HPK is a period of acceleration of child growth and development (gold period) which starts from the womb for 280 days of pregnancy until toddlerhood for 720 days or around 2 years. This period is a period that determines the quality of life so it is called the golden period. This period is a sensitive period because the consequences for children at this time will be permanent and cannot be corrected. For this reason, it is necessary to fulfill adequate nutrition at this age (Achadi, 2020). In the community service program implemented, it aims to empower cadres in overcoming stunting problems through promotive efforts through Counseling on Assessment of Child Growth and Development by practicing directly how to measure and weigh toddlers by the community service team. The result of community service is an increase in cadres' knowledge about stunting and its prevention. Furthermore, to increase cadres' knowledge about stunting, continuous educational efforts and regular cadres are needed Keywords: Counseling, Stunting